Tectonic uplifts based on morphometric indices in North West Sabah, Malaysia - Chung, Wei Kiat (2020)
The study constitutes the identification of uplift sites based on gradient and erosion anomalies over four major catchments in northwest Sabah, namely Kota Belud, Tuaran, Kinabalu Northeast, and Kinabalu Southeast catchments. The objectives of the study are to identify and screen regional sites of tectonic uplifts; identify and characterize sites of local uplift; validate the tectonic uplift in the field; and infer the active tectonics of northwest Sabah. The sites of tectonic uplifts at a regional and local scale were identified using gradient and erosion metrics over the 30 m resolution SRTM digital elevation models (DEM) and 5 m resolution IFSAR digital elevation models (DTM & DSM), respectively. The gradient metrics includes stream-length gradient index, surface-shape length gradient index, and knickpoint identifications whereas the erosion metrics includes normalized channel steepness index, chi-factor analysis and minimum bulk erosion. Based on the morphometric indices, several sites located both in the western and eastern flank catchments showed significant anomalies interpreted to be uplifted sites due to faults or lithological differences. Some of the anomalies are aligned N40E and may indicate alignment of regional faults. A closer analysis of some of the most significant anomalies in 18 sites clearly showed the presence of uplifted landforms. Out of 18 uplifted sites validated and characterized in the field, 11 sites from the western flank catchments indicates a NW-SE extensional regime, where the landform appears to be stretched forming a series of rapids and small waterfalls, whereas 7 sites from the eastern flank catchments indicates a NWSE compressional regime, where the landform appears to have buckled causing stream ponding and incised valleys. The presence of both compressional and extensional tectonic regimes in northwest Sabah may be associated with NW-SE intraplate compression and gravity sliding towards the South China Sea.